Physiotherapy students' and clinical teachers' perspectives on best clinical teaching and learning practices: A qualitative study. - D.V. Ernstzen; E. Bitzer; K. Grimmer-Somers (AOSIS, 2010)
Background: Clinical  education  forms  a  core  component of the training  of physiotherapy students.  Little research on the efficacy of commonly used  physiotherapy  clinical  learning  and  teaching  opportunities are available. Objective: This  paper  sought  to  identify  the  clinical  teaching  and  learning  opportunities  that  undergraduate  physiotherapy  students  and  clinical  teachers viewed as effective in enhancing learning, as well as the reasoning behind their views.Design: A qualitative research design was used.  Data was analyzed using content analysis.   Data was coded, cate gorized and conceptualized into key themes and patterns. Participants: All third year (n=40) and fourth year (n=40) physiotherapy students as well as their clinical teachers (n=37) were eligible to participate. Semi-structured individual interviews were conducted with a purposive sample consisting of six third-year students, six fourth-year students and six clinical teachers.  Results:  The  results  indicated  that  learning  is  best  facilitated  in  open,  relaxed  environments.Demonstrations  of patient management by teachers and students, discussion of patient cases, feedback and formative assessment were identified to be effective strategies to enhance development of clinical competence.  Conclusion: Clinical education, using focused and structured processes, could ensure that students are exposed to a range of learning opportunities for development of clinical competence.